Health-related quality of life of patients after mechanical valve replacement surgery for rheumatic heart disease in a developing country. Issue 1 (8th December 2014) - Thomson Mangnall, Linda J; Sibbritt, David W; Fry, Margaret; Windus, Melanie; Gallagher, Robyn D
Abstract : Objective: To evaluate the health-related quality of life (HRQoL) of people in Fiji (n=128) undergoing heart valve replacement (VR) surgery for rheumatic heart disease (RHD), conducted by Open Heart International. Methods: Patients who had undergone surgery from 1991 to 2009 (n=72) and patients undergoing surgery for the years 2010–2012 (n=56) were surveyed prospectively, preoperatively and/or postoperatively (the mean follow-up time 5.9 years) using the standard recall Short-Form 36, V.2 (SF-36v2) HRQoL Survey. Results: The sample had a mean age of 26.7 years and 56% (n=72) were women. Preoperative HRQoL is impaired but by early postoperative (1 year) there is significant improvement across all domains (p<0.05) apart from mental health (p=0.081). At mid-term (2 years), HRQoL remained substantially improved from preoperative measurement with mental health now significantly better (p=0.028). However, compared with the early follow-up outcomes, at mid-term physical function (p=0.001), role–physical (p=0.002) and role–emotional (p=0.042) domains significantly declined. By late follow-up (>2 years), all HRQoL domains, except for mental health, were significantly better than preoperative (p=0.066 ). Predictors of less improved HRQoL included having an isolated mitral valve replacement (MVR) (for six of eight health domains, p<0.05), older age (three domains; role–physical, vitality and bodily pain, p<0.05) and male gender (in the role–emotional domain, p<0.05). Conclusions: This first investigation of the HRQoL of people in a developing country after VR surgery for RHD found significant improvement from surgery with this improvement generally sustained. The lack of improvement in mental health requires further exploration as does the influence of an isolated MVR, age and gender.